A survey of a blown pack spoilage produced by Clostridium perfringens in vacuum–packaged wurstel. (April 2021) - Iacumin, Lucilla; Comi, Giuseppe
Abstract: Three hundred Clostridium strains were isolated from spoiled wurstels and were identified by traditional and molecular methods as Clostridium perfringens . The phenotypic characteristics of the strains were studied. All the strains produced acetic and butyric acids and enterotoxin. C. perfringens grew in the spoiled wurstels because it was present in raw meat (Lot 150) at a level of 3.2 log CFU/g due to an unchecked cooling phase that took 28 h to decrease the temperature of the wurstels from 60 to 9–10 °C, which is the lower limit for C. perfringens growth. During the 28 h of cooling, the concentration of C. perfringens increased to 6.5 CFU/g. It was concluded that its presence and the long cooling time were the main factors responsible for the spoilage. Wurstels intentionally made with contaminated meat (3 log CFU/g) but cooled after cooking for 17 h to 9 °C did not support C. perfringens growth; consequently, these wurstels remained unspoiled. The packages of the spoiled wurstels were blown, and the products were soft (soggy), textureless and had the odour of acetic acid, ethanol and sulfur. Highlights: Determination of Clostridium perfringens in spoiled wurstel. Characterization of the Clostridium perfringens strains. Characterization of the spoilage. Suggestions to prevent the spoilage.